Randomized controlled trial of three oxytocic regimens to prevent primary postpartum haemorrhage at caesarean section - Peea, AJ; Begum, F; Saha, E (Mediscope, 2017)
The objective of this present study was to compare the efficacy of three oxytocic regimens to prevent primary postpartum haemorrhage (PPH) at caesarean section. A randomized controlled trial including 90 patients who underwent caesarean section were selected according to inclusion and exclusion criteria assigned randomly into three groups (30 patients in each group) was conducted. Group 1 and group 2 were exposure groups and group 3 was control group. All patients were given 10 units intravenous (IV) bolus oxytocin immediately after delivery of baby. Group 1 was given additional 20 units oxytocin in each 1000 ml fluid for 24 hours. Group 2 received additional 1000 microgram misoprostol per rectal. Group 3 did not receive any additional oxytocic drug. Background characteristics of all the three groups were similar. It was observed that 501-1000 ml blood loss was found among 25 (83.3%) cases in group 1, 27 (90.0%) in group 2 and 27 (90.0%) in group 3. The mean (SD) amount of blood loss was found 733 (190) ml in group 1792 (187) ml in group 2 and 818 (14) ml in group 3. Occurrence of PPH and blood transfusion needed among 1 (3.3%) in group 1, 2 (6.7%) in group 2 and 3 (10.0%) in group 3. Side effects occurred in 7 (23.3%) patients of group 1, 18 (60.0%) in group 2, and 6 (20.0%) in group 3. Shivering was found among 4 (13.3%) in group 1, 10 (33.3%) in group 2 and 3 (10%) in group 3. Vomiting was found among 2 (6.7%) in group 1, 4 (13.3%) in group 2, and 2 (6.7%) in group 3. Pyrexia was 1 (3.3%) in group 1, 4 (13.3%) in group 2 and 1 (3.3%) in group 3. Side effects were more in the group where misoprostol was used. Except side effects there was no statistical difference of occurrence of different events among the three groups. Only bolus IV oxytocin appears to be as effective as oxytocin infusion in addition to bolus IV oxytocin or per rectal misoprostol in addition to bolus IV oxytocin to prevent primary PPH at caesarean section. But occurrence of transient side effects such as shivering, pyrexia and vomiting were noted more frequently with the use of misoprostol. Mediscope Vol. 4, No. 2: Jul 2017, Page 5-11